2021
DOI: 10.1007/s00604-021-04713-4
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric sensor based on long alkyl chain tetraalkylammonium ionic liquids comprising ascorbate anion for determination of nitrite

Abstract: An electrochemical sensor was fabricated utilizing ionic liquids possessing cations with long alkyl chains such as trimethyl octadecylammonium and behenyl trimethylammonium and ascorbate anion. The ionic liquids were drop-coated onto the electrode. Thin modifying layers were prepared. Cyclic voltammetric investigations revealed electrostatic interactions between the electrochemical probes and the modified surface, proving that a positive charge was established at the film surface. Hence, negatively charged spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The slope value of (log I p vs log v) was 0.87. This slope was an intermediate value between the theoretical value of 0.5 for diffusion-controlled process and close to the theoretical value, of 1, for the adsorption process, confirming that the oxidation process of the VILD was controlled by a combination of diffusion and adsorption process [52][53][54][55][56].…”
Section: Study Of the Potential Scan Rate Effectsupporting
confidence: 73%
See 1 more Smart Citation
“…The slope value of (log I p vs log v) was 0.87. This slope was an intermediate value between the theoretical value of 0.5 for diffusion-controlled process and close to the theoretical value, of 1, for the adsorption process, confirming that the oxidation process of the VILD was controlled by a combination of diffusion and adsorption process [52][53][54][55][56].…”
Section: Study Of the Potential Scan Rate Effectsupporting
confidence: 73%
“…A linear relationship between the I p / μA vs v/mV s −1 is expressed by an Eq. (2): Based on the good linearity of the I p /μA vs v/mV s −1 plot, suggested that the oxidation process was controlled by a combination of diffusion and adsorption processes [52][53][54][55][56].…”
Section: Study Of the Potential Scan Rate Effectmentioning
confidence: 99%
“…14 Further, ammonium-based ILs bearing a docosyl (C 22 ) chain were used in the fabrication of electrodes for use as sensors for nitrites. 15…”
Section: Introductionmentioning
confidence: 99%
“…To improve the electrochemical signal and the rapid response of electrochemical sensors, it is usually necessary to modify the electrode surface with appropriate functional materials. 39 Various electroactive materials have been used to modify bare electrodes to enhance their performance in detecting environmental pollutants. 40 In recent years, functional nanomaterials have been utilized to enhance the performance of electrodes.…”
Section: Introductionmentioning
confidence: 99%